2022
DOI: 10.1111/jonm.13671
|View full text |Cite
|
Sign up to set email alerts
|

Financial competencies as investigated in the nursing field: Findings of a scoping review

Abstract: Aim(s): This study aims to map the extent of the research activity in the field of financial competencies and nursing and identify main patterns, advances, gaps, and evidence produced to date. Background: Financial competencies are important indicators of professionalism and may influence the quality of care in nursing; moreover, these competencies are the basis of health care sustainability. Despite their relevance, studies available on financial competencies in the nursing field have not been mapped to date.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Similarly, a study by [11] revealed the prevalent unmet financial management needs in public health in the context of LMICs. Moreover, [12] reported a limited study of financial management competency in healthcare. This highlights the paucity of empirical research on financial management expertise at the primary healthcare level in LMICs [12,15,16,17] and this matter remains open for debate among researchers, policymakers and practitioners in the LMICs [13,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study by [11] revealed the prevalent unmet financial management needs in public health in the context of LMICs. Moreover, [12] reported a limited study of financial management competency in healthcare. This highlights the paucity of empirical research on financial management expertise at the primary healthcare level in LMICs [12,15,16,17] and this matter remains open for debate among researchers, policymakers and practitioners in the LMICs [13,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are significant knowledge gaps concerning the financial management skills of healthcare managers in LMICs, which need to be investigated [14,12] and this applies to Tanzania as well [13]. This research paper aims to address the questions related to the financial managerial skills of primary healthcare facility managers.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to recent years, financial and business skills weren't commonly introduced in undergraduate nursing curricula and were inconsistently introduced in nursing master's and doctoral programs. 10,11 This resulted in a lack of standardization in financial and business training for new nurse leaders. Additionally, nursing makes up the largest workforce in healthcare, requiring nurse leaders to be responsible for the largest operational budgets in most healthcare organizations.…”
mentioning
confidence: 99%
“…Traditionally, nurse leaders are promoted based on their clinical expertise rather than their business acumen. Prior to recent years, financial and business skills weren't commonly introduced in undergraduate nursing curricula and were inconsistently introduced in nursing master's and doctoral programs 10,11. This resulted in a lack of standardization in financial and business training for new nurse leaders.…”
mentioning
confidence: 99%